Investigating Indonesian EFL preservice teachers - Purwati, Diana; Fathirma'ruf, Fathirma'ruf; Lakehu, Amalia; Taufik, Taufik (Universitas Islam Negeri Palangka Raya, Indonesia, 2024)
The role of technology in learning English as a foreign language (EFL) remains significant. While numerous studies explored the effectiveness of technology in learning EFL, there is a paucity of research that examines EFL preservice teachers' digital technological awareness and their challenges in using technology in EFL learning. This study aims to investigate EFL preservice teachers' digital technological awareness and their challenges. This case study involved six EFL preservice teachers from the English Education Program at one of the higher colleges in West Nusa Tenggara Province, Indonesia. The data were garnered through in-depth interviews and observations. Thematic analysis was used to analyze the data. The result shows that teachers